Protective Effects of Chlorogenic Acid on Cerebral Ischemia/Reperfusion Injury Rats by Regulating Oxidative Stress-Related Nrf2 Pathway - Liu D; Wang H; Zhang Y; Zhang Z (Dove Medical Press, 2020)
Dequan Liu,1 Huilin Wang,1 Yangang Zhang,2 Zhan Zhang2 1Department of Neurology, Luoyang Central Hospital Affiliated to Zhengzhou University, Luoyang, Henan 471000, People’s Republic of China; 2Department of Ultrasound, The Affiliated Children’s Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, 710003, People’s Republic of ChinaCorrespondence: Zhan ZhangThe Affiliated Children’s Hospital of Xi’an Jiaotong University, No. 69, Xijuyuan Lane, Lianhu District, Xi’an City, Shaanxi Province 710003, People’s Republic of ChinaTel +86-29-13991941239Email o9al8i37sz3r@sina.comIntroduction: Cerebral ischemia-reperfusion (CI/R) injury is caused by blood flow recovery after ischemic stroke. Chlorogenic acid (CGA, 5-O-caffeoylquinic acid) is a major polyphenol component of Coffea canephora, Coffea arabica L. and Mate (Ilex paraguariensis A. StHil.). Previous studies have shown that CGA has a significant neuroprotective effect and can improve global CI/R injury. However, the underlying molecular mechanism of CGA in CI/R injury has not been fully revealed.Materials: In this study, CI/R rat model was constructed. The rats were randomly divided into nine groups with ten in each group: Control, CGA (500 mg·kg-1), CI/R, CI/R + CGA (20 mg·kg-1), CI/R + CGA (100 mg·kg-1), CI/R + CGA (500 mg·kg-1), ML385 (30 mg·kg-1), CI/R + ML385 (30 mg·kg-1), CI/R + CGA + ML385. Cerebral infarction volume was detected by TTC staining. Brain pathological damage was detected by H&E staining. Apoptosis of cortical cells was detected by TUNEL staining. The expression of related proteins was detected by RT-qPCR and Western blotting.Results: Step-down test and Y maze test showed that CGA dose-dependently mitigated CI/R-induced brain damage and enhanced learning and spatial memory. Besides, CGA promoted the expression of BDNF and NGF in a dose-dependent manner and alleviated CI/R-induced nerve injury. Moreover, CGA increased the activity of SOD and the level of GSH, as well as decreased production of ROS and LDH and the accumulation of MDA. Notably, CGA attenuated oxidative stress-induced brain injury and apoptosis and inhibited the expression of apoptosis-related proteins (cleaved caspase 3 and caspase 9). Additionally, CGA reversed CI/R induced inactivation of Nrf2 pathway and promoted Nrf2, NQO-1 and HO-1 expression. Nrf2 pathway inhibitor ML385 destroyed this promotion.Discussion: All the data indicated that CGA had a neuroprotective effect on the CI/R rats by regulating oxidative stress-related Nrf2 pathway.Keywords: cerebral ischemia/reperfusion injury, chlorogenic acid, oxidative stress, neuroprotection, NF-E2-related factor 2 pathway